Categorization of allergic disorders in the new World Health Organization International Classification of Diseases. Issue 1 (28th November 2014) - Tanno, Luciana Kase; Calderon, Moises A; Goldberg, Bruce J; Akdis, Cezmi A; Papadopoulos, Nikolaos G; Demoly, Pascal
Abstract: Background: Although efforts to improve the classification of hypersensitivity/allergic diseases have been made, they have not been considered a top‐level category in the International Classification of Diseases (ICD)‐10 and still are not in the ICD‐11 beta phase linearization. ICD‐10 is the most used classification system by the allergy community worldwide but it is not considered as appropriate for clinical practice. The Systematized Nomenclature of Medicine Clinical Terms (SNOMED CT) on the other hand contains a tightly integrated classification of hypersensitivity/allergic disorders based on the EAACI/WAO nomenclature and the World Health Organization (WHO) may plan to align ICD‐11 with SNOMED CT so that they share a common ontological basis. Methods: With the aim of actively supporting the ongoing ICD‐11 revision and the optimal practice of Allergology, we performed a careful comparison of ICD‐10 and 11 beta phase linearization codes to identify gaps, areas of regression in allergy coding and possibly reach solutions, in collaboration with committees in charge of the ICD‐11 revision. Results: We have found a significant degree of misclassification of terms in the allergy‐related hierarchies. This stems not only from unclear definitions of these conditions but also the use of common names that falsely imply allergy. The lack of understanding of the immune mechanisms underlying some of the conditions contributes to the difficulty in classification. Conclusions: More than providing data to support specific changes into the ongoing linearization, these results highlight the need for either a new chapter entitled Hypersensitivity/Allergic Disorders as in SNOMED CT or a high level structure in the Immunology chapter in order to make classification more appropriate and usable.